2020
DOI: 10.1038/s41598-020-78896-w
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin induced neurotoxicity is mediated by Sarm1 and calpain activation

Abstract: Cisplatin is a commonly used chemotherapy agent with significant dose-limiting neurotoxicity resulting in peripheral neuropathy. Although it is postulated that formation of DNA-platinum adducts is responsible for both its cytotoxicity in cancer cells and side effects in neurons, downstream mechanisms that lead to distal axonal degeneration are unknown. Here we show that activation of calpains is required for both neurotoxicity and formation of DNA-platinum adduct formation in neurons but not in cancer cells. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…In addition, mouse models of paclitaxel have shown that axonal degeneration occurs in the central and peripheral axon branches of DRG cells (Tasnim et al, 2016). Axonal blebbing and degeneration have been reported in other studies of 50B11 cells treated with cisplatin (Cetinkaya-Fisgin et al, 2020). Our study demonstrated occurrence of axonal blebbing and decreased neurite length in DRG sensory cells after paclitaxel treatment.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, mouse models of paclitaxel have shown that axonal degeneration occurs in the central and peripheral axon branches of DRG cells (Tasnim et al, 2016). Axonal blebbing and degeneration have been reported in other studies of 50B11 cells treated with cisplatin (Cetinkaya-Fisgin et al, 2020). Our study demonstrated occurrence of axonal blebbing and decreased neurite length in DRG sensory cells after paclitaxel treatment.…”
Section: Discussionsupporting
confidence: 83%
“…Certainly, animal model studies suggest so. SARM1 deletion alleviates chemotherapy-induced peripheral neuropathy with vincristine, paclitaxel, bortezomib, cisplatin and oxaliplatin and neuropathy in a type 2 diabetes model using a high fat diet [ 157 , 158 , 208 , 214 , 226 , 227 ], all of which suggest relevance to more common disorders of peripheral nerve. Association with idiopathic peripheral neuropathy, inflammatory neuropathies and other toxic neuropathies, building on findings with vacor as well as cancer chemotherapy drugs will also be important to explore.…”
Section: Future Perspectives: Outstanding Questionsmentioning
confidence: 99%
“…Injured or diseased axons initiate a self-destruction program known as Wallerian degeneration. SARM1 triggers this pathological axon degeneration (1), and is a key driver of pathology in models of chemotherapy-induced peripheral neuropathy (2)(3)(4)(5), traumatic brain injury (6)(7)(8)(9)(10), glaucoma (11), and retinal degeneration (12,13). SARM1 also participates in antiviral defense.…”
Section: Introductionmentioning
confidence: 99%